ANALISA KEPUASAN PELANGGAN TERHADAP PRODUK DAN LAYANAN DI LE BLÉ BOULANGERIE SURABAYA - Samantha Jane Hampton; Sherryn Sheronna; Agoes Tinus Lis Indrianto; Ivana Grasielda (JURNAL ILMIAH EDUNOMIKA, 2026)
This study seeks to examine customer satisfaction with the products and services offered at Le Blé Boulangerie Surabaya. Customer satisfaction serves as a key measure of business performance, indicating the extent to which a company fulfills or surpasses customer expectations. A qualitative case study approach was employed to gain an in-depth understanding of customers’ perceptions and experiences. Data were gathered through in-depth interviews, observations, and documentation, involving both new and repeat customers, as well as internal stakeholders. The results reveal that customer satisfaction is shaped by several important factors, including product quality (such as taste, presentation, and variety), service quality, pricing, café ambiance, and location. Most customers expressed satisfaction with the consistency and quality of the products, along with the friendly and responsive service provided. Furthermore, emotional aspects such as comfort and overall atmosphere significantly contribute to the level of satisfaction experienced by customers. The study concludes that sustaining high product quality, enhancing service consistency, and continuously innovating menu offerings are crucial strategies for increasing customer satisfaction and fostering customer loyalty. These findings are expected to offer practical insights for improving customer experience within the culinary business industry.